HISTOPATHOLOGICAL OF WHITE RATS SPLEEN THAT GIVEN DEXAMETHASONE AND VITAMIN E - Hidayati, Elsa; Berata, I Ketut; Samsuri, Samsuri; Sudimartini, Luh Made; Merdana, I Made (Buletin Veteriner Udayana, 2018)
Dexamethasone is a corticosteroid drug from the class of glucocorticosteroids that has anti-inflammation and immunosuppressant effect. This drug has therapeutic effect such as immunosuppressive and reducing the inflammatory response. Spleen is an organ of the immune system, so that when used dexamethasone in the long term and large doses can affect the spleen. To prevent dexamethason effect on spleen, provision of antioxidants is required. Vitamin E is a fat soluble vitamin that acted as antioxidant. This study used complete randomized design. Sample of this experiment were 25 male rats divided randomly into 5 groups. Negative control were given standards food and drink. Dexamethasone administrated by subcutaneous injection 0,13 mg/kg BW in  positive control group, P1, P2 and P3. Vitamin E administrated orally with following P1 (100 mg/kg BW), P2 (150 mg/kg BW) and P3 (200 mg/kg BW). After 2 weeks intervention, all samples were terminated, then took the spleen to make histopatology preparation. The variables examined include hemorrhage and necrosis. From the results showed a positive control necrosis, whereas P1, P2, P3 improvements in spleen damage, but was not significant. P2 treatment showed the best results in reducing the effects of dexamethasone. From this study it can be concluded that the dexamethasone dose 0,13 mg/kg BW has histopatology of spleen changes and vitamin E dose 150 mg/kg BW can repair spleen tissue damage is better than vitamin E dose 100 mg/kg BW and 200 mg/kg BW.